Sociodemographic characterization, clinical and cognitive profile of patients with Heart Failure (Research, Society and Development, 2021)
Heart failure (HF) is considered one of the main health problems in the world. This fact draws attention to the need to know and expand discussions about the variables that are correlated to the development of this disease. The objective was to characterize socioeconomic, clinical and cognitive variables of patients with HF. Cross-sectional, quantitative and descriptive study, composed of patients with HF hospitalized in the wards of the Hospital de Beneficência in Surgery, over a 12-month period between 2018 and 2019. Interviews were used to apply a clinical and questionnaire questionnaire. sociodemographic and evaluation of the Mini Mental State Examination (MMSE). One hundred patients with a mean age of 59 ± 15 years, 51% female, were included. Family income mostly up to one minimum wage (57%), schooling from one to seven years (41%). As for clinical aspects, 34% had HF for more than five years, 40% had valve etiology, 51% had a class III functional classification, 43% had systemic arterial hypertension, 37% had undergone cardiac surgery in the last year, and 13% had angioplasty as most performed invasive procedure. Regarding the MMSE, the mean was 21±6 points, with high scores in the domains evaluated separately, except for “attention and calculation” and “recalling memory”. The socioeconomic and clinical profile, in addition to the cognitive status can help guide the management of patients, in order to manage therapy according to the different specificities of each patient.